Classification of Industrial Heat Consumers for Integration of Solar Heat. (June 2016) - Schmitt, Bastian
Abstract: In spite of the large potential, the market development of solar heat for industrial or commercial applications is rather slow so far. An important barrier for the market development is the large effort to carry out a feasibility assessment including the pre-dimensioning of a suitable solar process heat system. Especially to facilitate the identification of suitable integration points for solar heat in Industry, tools and guidelines are required. To reduce the effort for identification of a suitable integration point within Industry, comprehensive research on the food and beverages sector was performed to highlight the possibilities for integrating solar heat. The analysis shows that the utilized process installations and especially the current equipment for heating are of particular importance for the integration of solar heat. Based on the results of the analysis of several sectors of the food and beverage industry and conventional process heating technologies, a classification for the integration of solar heat in industrial processes and heat supply systems was developed. This classification is sector independent and contains concepts for the hydraulic integration of solar heat for the majority of all industrial processes and operations. Finally, an approach is presented to simplify the choice of a suitable integration point for solar heat in industry. This approach includes the identification and assessment of possible integration points as well as the utilization of the developed classification and other important steps within the feasibility assessment.